Russian and chinese student basketball teams: personality profiles versus the competitive success rates - Shumova, N. S.; Baykovsky, Y. V.; Siuntse, L. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to make a comparative analysis of the personality profiles versus the competitive success rates of the Russian and Chinese student basketball teams. Subject to the study were the Russian State University of Physical Education, Sports, Youth and Tourism (SCOLIPE) team ((n=15, Russia) and Beijing Sport University team (n=15, China) of 18-23 year olds having the sport records of 5-13 years and qualified Class II to Candidate Masters of Sport. Applied for the study purposes were 6 popular (widely used in Russia and abroad) mental performance tests generating 82 test rates. Based on the study data and analysis we found that the Chinese team leaders are less prone to control the teamwork and prefer working hard on their own for competitive success. Extraverted players in the Russian team were tested to effectively cement the teamwork i.e. consolidate the individual performances by active own mental efforts to inspire the team with their ideas. Competitive success of the Russian team was found largely due to the mental pressure and control of the field-dependent team members by the field-independent ones.